Carotid Doppler ultrasound for non-invasive haemodynamic monitoring: a narrative review. (1st March 2023) - Suriani, Irene; van Houte, Joris; de Boer, Esmée C; van Knippenberg, Luuk; Manzari, Sabina; Mischi, Massimo; Bouwman, R Arthur
Abstract: Objective. Accurate haemodynamic monitoring is the cornerstone in the management of critically ill patients. It guides the optimization of tissue and organ perfusion in order to prevent multiple organ failure. In the past decades, carotid Doppler ultrasound (CDU) has been explored as a non-invasive alternative for long-established invasive haemodynamic monitoring techniques. Considering the large heterogeneity in reported studies, we conducted a review of the literature to clarify the current status of CDU as a haemodynamic monitoring tool. Approach. In this article, firstly an overview is given of the equipment and workflow required to perform a CDU exam in clinical practice, the limitations and technical challenges potentially faced by the CDU sonographer, and the cerebrovascular mechanisms that may influence CDU measurement outcomes. The following chapter describes alternative techniques for non-invasive haemodynamic monitoring, detailing advantages and limitations compared to CDU. Next, a comprehensive review of the literature regarding the use of CDU for haemodynamic monitoring is presented. Furthermore, feasibility aspects, training requirements and technical developments of CDU are addressed. Main results. Based on the outcomes of these studies, we assess the applicability of CDU-derived parameters within three clinical domains (cardiac output, volume status, and fluid responsiveness), and amongst different patient groups. Finally, recommendations are provided to improve the quality and standardization of future research and clinical practice in this field. Significance. Although CDU is not yet interchangeable with invasive 'gold standard' cardiac output monitoring, the present work shows that certain CDU-derived parameters prove promising in the context of functional haemodynamic monitoring.